Diagnoses and Outcomes of Prosthetic Replacement of the Ocular Surface Ecosystem Treatment—A Canadian Experience. Issue 7 (July 2021) - Wong, Bryan M.; Garg, Anubhav; Trinh, Tanya; Mimouni, Michael; Ramdass, Stephanie; Liao, Jennifer; Chandrakumar, Manokaraananthan; Chan, Clara C.; Slomovic, Allan R.
Abstract : Objectives: To investigate underlying diagnoses and outcomes of patients undergoing Prosthetic Replacement of the Ocular Surface Ecosystem (PROSE) treatment at the first Canadian PROSE center. Methods: A retrospective chart review was conducted on patients referred for PROSE treatment and fitted with PROSE devices from 2018 to 2020. Data were collected on diagnoses, presenting symptoms, previous lens modalities attempted, best-corrected visual acuities (BCVAs) pre-PROSE and post-PROSE, daily wear time, and failure rates. Best-corrected visual acuities pre-PROSE and post-PROSE were compared to evaluate visual improvement. Results: In total, 78 patients (126 eyes) were analyzed. The most common diagnoses were keratoconus (n=39 eyes) and postcorneal graft (n=15) in the distorted cornea group, and limbal stem cell deficiency (n=17) and graft versus host disease (n=15) in the ocular surface disease (OSD) group. Most frequent symptoms included blur, photophobia, and pain. Most common lens modalities attempted pre-PROSE were conventional scleral lenses and glasses. The overall mean BCVA improvement was 0.40 logarithm of the minimal angle of resolution (logMAR) (4-lines Snellen) ( P <0.0001). Best-corrected visual acuities improvement in the distorted cornea group (0.52 logMAR, 5-lines) was significantly greater than in the OSD group (0.29 logMAR, 3-lines) ( P =0.004). Conclusions: Prosthetic replacement of the ocular surface ecosystem treatment can provide significant visual improvement for patients with distorted corneal surfaces and OSDs who failed other lens modalities.